Towards an Ontology to Structure Data on Women's Leadership in Computing in Brazil - Martins, Thamires Faleiro (2023)
This paper proposes an ontology to structure data on female leadership in computer science in Brazil, with the goal of building an open and collaborative platform where data can be collected, organized, and classified to construct a folksonomy of the domain. The ontology aims to address competency questions in the domain, such as the contextual factors that motivate Brazilian women to pursue leadership positions in computer science, and the policies that promote such opportunities. The proposed ontology may benefit various users, including female computer science professionals, leaders, researchers, and policymakers.